Chăm sóc bệnh nhân ung thư đại trực tràng được hóa trị - Hạnh, Phạm Thị Hồng; Trang, Nguyễn Thị Diệu; Hoa, Châu Thị; Thanh, Đậu Thị; Châu, Phan Thị Ái; Anh, Phạm Thị Vân (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.